The underlying mechanism behind quest for significance and its role in violence extremism: A systematic literature review - Firdiani, Norberta Fauko; Milla, Mirra Noor; Hudiyana, Joevarian (Buletin Psikologi, 2025)
Based on the Quest for Significance Theory (SQT), violent extremism is a consequence of the quest for significance activated by significance loss, significance gain, and threat of significance loss. This systematic literature review aims to synthesize previous research related to the quest for significance using SQT. The authors selected 103 articles, and 24 articles met the inclusion criteria. The review results indicate that loss of significance consistently tends to activate the quest for significance and predicts violent extremism stemming from various factors, including vulnerable environments, perceptions of injustice, social rejection, and failure to achieve goals. Conversely, significance gain shows inconsistency; studies suggest this factor strengthens, weakens, or predicts future involvement in violent extremism. There has been no empirical research specifically addressing the threat of significance loss. The measurement of significance loss and significance gain has not been clearly distinguished and uses various proxies, indicating that standardized measurement tools have not yet been established. Additionally, there is still overlap in the operationalization of measurement between significance loss and the quest for significance.